Carbon dot/polyvinylpyrrolidone hybrid nanofibers with efficient solid-state photoluminescence constructed using an electrospinning technique. (11th December 2017) - Zhai, Yue; Bai, Xue; Cui, Haining; Zhu, Jinyang; Liu, Wei; Zhang, Tianxiang; Dong, Biao; Pan, Gencai; Xu, Lin; Zhang, Shuang; Song, Hongwei
Abstract: Carbon dots (CDs) are the promising candidates for application in optoelectronic and biological areas due to their excellent photostability, unique photoluminescence, good biocompatibility, low toxicity and chemical inertness. However, the self-quenching of photoluminescence as they are dried into the solid state dramatically limits their further application. Therefore, realizing efficient photoluminescence and large-scale production of CDs in the solid state is an urgent challenge. Herein, solid-state hybrid nanofibers based on CDs and polyvinylpyrrolidone (PVP) are constructed through an electrospinning process. The resulting solid-state hybrid PVP/CD nanofibers present much enhanced photoluminescence performance compared to the corresponding pristine colloidal CDs due to the decrease in non-radiative recombination of electron–holes. Owing to the suppressed self-quenching of CDs, the photoluminescence quantum yield is considerably improved from 42.9% of pristine CDs to 83.5% of nanofibers under the excitation wavelength of 360 nm. This has great application potential in optical or optoelectronic devices.